Gendered lived experiences of marriage and family following exposure to chemical warfare agents: content analysis of qualitative interviews with survivors in Halabja, Kurdistan-Iraq - Anna-Carin Olin; Faraidoun Moradi; Fazil Moradi; Mia Söderberg; Mona Lärstad (BMJ Open)
Objective To study gendered experiences of the long-term effects of a chemical warfare agent (CWA; sulfur mustard).Design Qualitative face-to-face semi-structured in-depth interview study using content analysis approach with thematic analysis and anthropological inquiries.Setting The city of Halabja in the Kurdistan Region of Iraq.Participants Survivors of CWA (n=16, female:male 10:6, mean age 45.5 years (range 34 to 67)) with lung damage diagnosis and with a range of sociodemographic variables.Results Latent content was expressed as: To get or not to get married? Two categories—social abandonment and uncertain marriage—emerged as expressions of the manifest content. The majority of the participants showed uncertainty as a central concern that affects all decision-making in their private and social life. Uncertainty over marriage and family were huge, corresponding to their fear of giving birth to children with congenital birth defects. Exposure to CWAs was conceptualised in terms of stigmatised illnesses, and consequently resulted in loneliness and social isolation, leading to negative impacts on other aspects of professional and social life. The results demonstrated a gendered pattern: CWA-exposed women were more affected psychosocially than CWA-exposed men. More CWA-exposed women were unemployed, divorced or single, or lived under vulnerable circumstances compared with men.Conclusion Survivors of CWA exposure have developed a sense of gendered uncertainty around getting married and building a family. Sulfur mustard-exposed women, in particular, long to be desired in the community as they face social exclusion. Survivors should be provided evidence-based consultancy to optimise their decision-making around marriage and other social and family challenges.